Sec22b-dependent antigen cross-presentation is a significant contributor of T cell priming during infection with the parasite Trypanosoma cruzi - Biscari, Lucía; Maza, Ma Carmen; Farré, Cecilia; Kaufman, Cintia Daniela; Amigorena, Sebastian; Fresno, Manuel; Gironès, Núria; Alloatti, Andrés (Frontiers in Cell and Developmental Biology, 2023)
Antigen cross-presentation is a vital mechanism of dendritic cells and other antigen presenting cells to orchestrate the priming of cytotoxic responses towards killing of infected or cancer cells. In this process, exogenous antigens are internalized by dendritic cells, processed, loaded onto MHC class I molecules and presented to CD8+ T cells to activate them. Sec22b is an ER-Golgi Intermediate Compartment resident SNARE protein that, in partnership with sintaxin 4, coordinates the recruitment of the transporter associated with antigen processing protein and the peptide loading complex to phagosomes, where antigenic peptides that have been proteolyzed in the cytosol are loaded in MHC class I molecules and transported to the cell membrane. The silencing of Sec22b in dendritic cells primary cultures and conditionally in dendritic cells of C57BL/6 mice, critically impairs antigen cross-presentation, but neither affects other antigen presentation routes nor cytokine production and secretion. Mice with Sec22b conditionally silenced in dendritic cells (Sec22b-/-) show deficient priming of CD8+ T lymphocytes, fail to control tumor growth, and are resistant to anti-checkpoint immunotherapy. In this work, we show that Sec22b-/- mice elicit a deficient specific CD8+ T cell response when challenged with sublethal doses of Trypanosoma cruzi trypomastigotes that is associated with increased blood parasitemia and diminished survival.